Nano carbon layer modified graphite felt electrode for all-vanadium redox flow battery as well as preparation method and application of nano carbon layer modified graphite felt electrode

The construction of nanocarbon layers on the surface of graphite felt through heat treatment and magnetron sputtering technology has solved the problem of insufficient electrochemical performance of carbon-based electrode materials in all-vanadium liquid flow batteries, and achieved efficient modification of electrode materials and improved battery performance.

CN119230857APending Publication Date: 2024-12-31XI AN JIAOTONG UNIV
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411383779.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The existing carbon-based electrode materials have problems such as poor electrochemical reaction activity and insufficient kinetic reversibility in all vanadium flow batteries. The preparation process is difficult, time-consuming, and costly. The nanomaterial size is large and the distribution is uneven. , it is difficult to effectively improve electrochemical properties.

Method used

Premodified graphite felts are used to heat treatment, and nanocarbon layers are constructed on its surface through unbalanced magnetron sputtering and high-power pulse magnetron sputtering power supply, introducing active structures and oxygen functional groups to form multi-stage active structures and improving the electrode material Electrochemical reactivity and conductivity.

Benefits of technology

It significantly improves the electrochemical reaction activity and reversibility of the electrode, improves the energy efficiency of the battery, reduces the preparation cost, is simple and easy to operate, and is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119230857A_ABST
    Figure CN119230857A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of flow batteries, and discloses a nano-carbon layer modified graphite felt electrode for an all-vanadium flow battery, and a preparation method and application of the nano-carbon layer modified graphite felt electrode. The preparation method comprises the following steps: carrying out heat treatment on a graphite felt to form runner structures which are arranged in parallel on the surface of the graphite felt; and then glow discharge cleaning treatment is conducted under the vacuum condition, a closed field unbalanced magnetron sputtering ion plating technology is adopted, a HiPIMS power source is adopted for sputtering the graphite target material, a functional nano carbon layer is deposited on the surface of the flow channel structure arranged in parallel, and therefore the nano carbon layer modified graphite felt electrode with the multi-stage active structure on the surface is obtained. The preparation method has the advantages of mild conditions, simple process, easy operation, easily available raw materials, low preparation cost, and easy industrial production; the nano carbon layer modified graphite felt electrode has excellent electrochemical reaction activity, electrochemical reaction reversibility, conductivity, wettability to electrolyte and electrochemical performance stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of all-vanadium redox flow batteries, and in particular to a nano-carbon layer modified graphite felt electrode for all-vanadium redox flow batteries, and a preparation method and application thereof. Background Art

[0002] Vanadium redox flow batteries (VRFBs) are considered one of the most promising candidate technologies for large-scale energy storage due to their high storage capacity and output power, long cycle life, high safety, and low maintenance costs. VRFBs utilize the redox reaction of vanadium in the positive and negative electrodes to convert electrical energy into chemical energy, effectively avoiding cross-contamination of the positive and negative electrolytes.

[0003] VRFBs typically use carbon-based materials as electrode materials, including carbon cloth, carbon paper, and graphite felt, due to their low cost, high conductivity, high porosity, and corrosion resistance. Graphite felt, woven from carbon fibers, has become the primary choice for vanadium redox flow battery electrode materials due to its excellent chemical stability, high mechanical strength, and large electrochemical reaction area. However, carbon-based electrode materials have inherent drawbacks, such as poor electrochemical reactivity and insufficient kinetic reversibility.

[0004] Over the years, people have conducted extensive research on the modification of electrodes to improve their electrochemical performance. Surface treatment is one of the common modification methods. For example, the introduction of oxygen-containing functional groups through plasma treatment, heat treatment, acid treatment, etc. can effectively promote the increase of surface active sites and hydrophilicity, thereby improving the electrochemical performance of VRFB. In addition, the introduction of catalysts on the electrode surface is also an effective strategy to improve electrode performance. In recent years, metal oxides such as TiO2, ZrO2, Mn3O4 and WO3 have created high catalytic activity while breaking the cost limitations brought by precious metal catalysts. However, the poor conductivity and binding force of metal oxides hinder their application in long-term operation.

[0005] In order to overcome these shortcomings, carbon-based electrocatalytic nanomaterials, including graphene, carbon nanotubes, carbon nanosheets, etc., are used to modify the electrode surface. At present, the existing technology mainly uses mechanical exfoliation, chemical vapor deposition CVD, epitaxial growth and liquid phase exfoliation methods for the preparation of carbon-based electrocatalytic nanomaterials. Although the above methods can realize the modification of carbon-based electrocatalytic nanomaterials on the surface of carbon-based electrodes, the preparation process is difficult to operate, time-consuming, and the preparation cost is high. In addition, the carbon-based electrocatalytic nanomaterials modified on the surface of carbon-based electrodes are large in size and unevenly distributed, making it difficult to effectively improve the electrochemical reaction activity of carbon-based electrode materials, hindering their practical application in all-vanadium liquid flow batteries. Summary of the Invention

[0006] In order to solve the above-mentioned technical problems, the present invention provides a nano-carbon layer modified graphite felt electrode for all-vanadium liquid flow batteries, and its preparation method and application. The present invention uses graphite felt as a substrate, adopts a heat treatment method to pre-modify the graphite felt, and constructs a nano-carbon layer with an active structure on the graphite felt with the help of unbalanced magnetron sputtering and a high-power pulsed magnetron sputtering power supply. Since the present invention introduces a nanostructured carbon layer and rich oxygen functional groups on the electrode surface, the electrochemical sites on the electrode surface are enriched through a multi-level active structure, thereby improving the electrochemical reaction activity and reversibility of the electrode material. At the same time, the conductivity and wettability of the battery electrode material to the electrolyte are also improved. Among them, the full English name of high-power pulsed magnetron sputtering is High Power Impulse Magnetron Sputtering, which is usually referred to as HiPIMS in the art. Therefore, the present invention will use "HiPIMS power supply" to represent "high-power pulsed magnetron sputtering power supply" below.

[0007] The nano-carbon layer modified graphite felt electrode for all-vanadium redox flow battery of the present invention and its preparation method and application are achieved through the following technical solutions:

[0008] The first object of the present invention is to provide a method for preparing a nano-carbon layer modified graphite felt electrode for an all-vanadium redox flow battery, comprising the following steps:

[0009] Step 1: Pre-modification of graphite felt:

[0010] The graphite felt is used as a substrate, and the cleaned graphite felt is heat-treated to form a parallel flow channel structure on the surface of the graphite felt to obtain a pre-modified graphite felt.

[0011] It should be noted that in order to prevent the impurities that may exist in the graphite felt from affecting the subsequent modification of the graphite felt surface, the present invention cleans the graphite felt and then dries it before heat-treating it to obtain clean graphite felt. Among them, in some preferred embodiments of the present invention, the specific operation of cleaning is: ultrasonically clean the porous graphite felt with deionized water at least twice, and then ultrasonically clean the porous graphite felt with anhydrous ethanol at least twice, each cleaning lasting more than 5 minutes, and replace the cleaning agent before the next cleaning. Among them, the specific drying process parameters are not limited, as long as the residual solvent from washing can be dried and removed, for example: the cleaned graphite felt is placed in a vacuum oven with a preset temperature of 80°C and dried for 6 hours.

[0012] The present invention adopts a method of washing and then drying to clean the graphite felt, which not only can remove impurities from the graphite felt and improve the purity of the graphite felt, but also drying can increase the surface defects, specific surface area and reaction active sites of the graphite felt fibers, which is beneficial for the subsequent heat treatment to make the fiber surface of the graphite felt present a structure with multiple flow channels arranged in parallel, thereby facilitating the wetting of the electrolyte on the electrode surface and the reaction of active substances on the electrode surface.

[0013] In order to ensure that the fiber surface of the graphite felt can be processed into a flow channel structure with multiple flow channels arranged in parallel by heat treatment, in some preferred embodiments of the present invention, the heat treatment temperature is 400℃~600℃, the heat treatment time is 3h~6h, and the heat treatment heating rate is 5℃·min -1 ~10℃·min -1 .

[0014] Step 2: Sputtering the carbon layer using closed-field unbalanced magnetron sputtering ion plating technology:

[0015] Under vacuum conditions, the pre-modified graphite felt is subjected to glow discharge cleaning treatment; subsequently, under vacuum conditions, a HiPIMS power supply is used as a sputtering power supply, a graphite target is used as a carbon layer deposition source, and a closed-field unbalanced magnetron sputtering ion plating technology is used for sputtering treatment to deposit a layer of functional nanocarbon layer on the surface of the pre-modified graphite felt after the glow discharge cleaning treatment, thereby obtaining the functional nanocarbon layer modified graphite felt electrode with a multi-level active structure.

[0016] It should be noted that, in order to facilitate the glow discharge cleaning and sputtering treatments, in some preferred embodiments of the present invention, the pre-modified graphite felt is fixed on a sample turntable in a vacuum chamber of a closed-field unbalanced magnetron sputtering ion plating device, the turntable speed is set to 3 rpm to 6 rpm, and then the vacuum operation is performed until the background vacuum is <4×10 -3 Pa, and then glow discharge cleaning and sputtering are performed in sequence.

[0017] In some preferred embodiments of the present invention, when performing glow discharge cleaning treatment, argon gas is introduced into the vacuum chamber with a flow rate of 25 sccm to 40 sccm, the pressure inside the vacuum chamber is controlled to be 0.1 Pa to 0.2 Pa, a pulse bias of -400 V to -200 V is applied to the sample, and the pre-modified graphite felt is glow discharged cleaned with argon plasma for 10 min to 30 min.

[0018] In some preferred embodiments of the present invention, during sputtering, the vacuum chamber pressure is maintained at 0.1 Pa to 0.2 Pa, the pulse bias voltage is adjusted to -100 V to -70 V, the average power is controlled to 2 kW to 4 kW, and the deposition time is 0.5 to 5 hours. During the sputtering deposition process, carbon atoms sputtered from the target surface continuously accumulate on the surface of the graphite felt fibers, and the surface morphology thereof is primarily determined by the parallel flow channel structure formed by the pre-modified graphite felt fibers and the duration of the sputtering process. In some preferred embodiments of the present invention, by controlling the sputtering time, a functional nanocarbon layer is deposited on the surface of the pre-modified graphite felt after glow discharge cleaning. This results in a multi-level active structure formed by the surface having the parallel flow channel structure and the introduced nanocarbon layer, thereby obtaining the nanocarbon layer-modified graphite felt electrode for the all-vanadium liquid flow battery.

[0019] In some preferred embodiments of the present invention, during the sputtering process, the purity of the graphite target is ≥99.99% to ensure that a high-purity functional nano-carbon layer can be formed.

[0020] In some preferred embodiments of the present invention, during the sputtering process, the sputtering gas used is argon with a purity of ≥99.99%.

[0021] In some preferred embodiments of the present invention, during the sputtering process, the average power delivered by the HiPIMS power supply to a single graphite target is 40 kW to 60 kW.

[0022] The second object of the present invention is to provide a nano-carbon layer modified graphite felt electrode for all-vanadium redox flow battery prepared by the above preparation method.

[0023] The third object of the present invention is to provide an application of the above-mentioned nano-carbon layer modified graphite felt electrode for all-vanadium redox flow battery in an all-vanadium redox flow battery.

[0024] In some preferred embodiments of the present invention, the nano-carbon layer modified graphite felt electrode for all-vanadium redox flow battery prepared above is used as the electrode.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] The present invention uses graphite felt as a substrate, cleans it and then performs heat treatment to achieve pre-modification of the graphite felt, thereby obtaining a pre-modified graphite felt having a parallel flow channel structure on the surface. Then, with the help of unbalanced magnetron sputtering and HiPIMS power supply, a nano-carbon layer with an active structure is further constructed on the pre-modified graphite felt having a parallel flow channel structure on the surface, and then a nano-structured carbon layer and rich oxygen functional groups are introduced on the surface of the graphite felt, thereby forming a multi-level active structure through the surface with the parallel flow channel structure and the introduced nano-carbon layer, and then enriching the electrochemical sites on the surface of the graphite felt through the multi-level active structure, thereby improving the electrochemical reaction activity and reversibility of the electrochemical reaction of the graphite felt electrode material, and at the same time improving the conductivity and wettability of the graphite felt to the electrolyte when used as an electrode material. The preparation method of the present invention has relatively mild conditions, a simple and easy-to-operate process, readily available raw materials, low preparation costs, and is easy to industrialize.

[0027] The present invention adopts a method of washing and then drying to clean the graphite felt, which not only can remove impurities from the graphite felt and improve the purity of the graphite felt, but also drying can increase the surface defects, specific surface area and reaction active sites of the graphite felt fibers, which is beneficial for the subsequent heat treatment to make the fiber surface of the graphite felt present a structure with multiple flow channels arranged in parallel, thereby facilitating the wetting of the electrolyte on the electrode surface and the reaction of active substances on the electrode surface.

[0028] The all-vanadium redox battery assembled with the nano-carbon layer-modified graphite felt electrodes prepared by the present invention significantly reduces polarization during the redox process, significantly improves redox reversibility, and significantly enhances the energy efficiency of the all-vanadium redox battery. This addresses the technical issues that hinder the use of traditional carbon-based electrode materials as electrode materials for all-vanadium redox batteries due to inherent defects such as poor electrochemical reaction activity and insufficient kinetic reversibility. Furthermore, the nano-carbon layer-modified graphite felt electrodes prepared by the present invention exhibit excellent electrochemical performance stability, promoting the application of carbon-based materials as electrode materials for all-vanadium redox batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is a scanning electron microscope image of the nano-carbon layer modified graphite felt electrode prepared in Example 1; Figure 1 In the figure, Figure a is a scanning electron microscope image of the nano-carbon layer modified graphite felt electrode prepared in Example 1 at a scale of 20 μm, Figure b is a scanning electron microscope image of the nano-carbon layer modified graphite felt electrode prepared in Example 1 at a scale of 5 μm, and Figure c is a scanning electron microscope image of the nano-carbon layer modified graphite felt electrode prepared in Example 1 at a scale of 500 nm.

[0030] Figure 2This is a comparison chart of cyclic voltammetry curves of the nano-carbon layer modified graphite felt electrode of Example 1, the nano-carbon layer modified graphite felt electrode of Example 2, the modified graphite felt of Comparative Example 1, and the original graphite felt of Comparative Example 2 when used as positive electrodes.

[0031] Figure 3 This is a comparison chart of cyclic voltammetry curves of the nano-carbon layer modified graphite felt electrode of Example 1, the nano-carbon layer modified graphite felt electrode of Example 2, the modified graphite felt of Comparative Example 1, and the original graphite felt of Comparative Example 2 when used as negative electrodes.

[0032] Figure 4 The vanadium redox flow batteries corresponding to Example 1, Example 2, Comparative Example 1 and Comparative Example 2 are at 50 mA·cm -2 ~250mA·cm -2 Energy efficiency test results at current density of .

[0033] Figure 5 The vanadium redox flow battery corresponding to Example 1 and Comparative Example 2 is 150 mA·cm -2 The stability test results of coulombic efficiency and energy efficiency at current density. DETAILED DESCRIPTION

[0034] The technical solutions in the embodiments of the present invention will be described clearly and completely below. It should be noted that the graphite felts used in the following embodiments of the present invention are all graphite felts specially used for flow batteries and are purchased from Liaoning Jingu Carbon Materials Co., Ltd. The closed-field unbalanced magnetron sputtering ion plating device used in the following embodiments of the present invention is manufactured by Teer Coatings Ltd. in the UK. The closed-field unbalanced magnetron sputtering ion plating device used is equipped with a HiPIMS power supply, which can deliver an average power of 40kW to 60kW to a single target.

[0035] Example 1

[0036] This embodiment provides a nano-carbon layer modified graphite felt electrode for an all-vanadium redox flow battery, which is prepared by the following steps:

[0037] Step 1: Pre-modification of graphite felt:

[0038] 1) Cut the graphite felt into 3 cm × 3 cm squares and ultrasonically clean them twice with deionized water and anhydrous ethanol, respectively, with each cleaning lasting more than 5 minutes.

[0039] 2) The cleaned graphite felt was placed in a vacuum oven at a preset temperature of 80° C. and dried for 6 h to obtain clean and dry graphite felt.

[0040] 3) Place the clean and dry graphite felt in a muffle furnace and heat it at 5℃·min -1The temperature was raised to 600°C at a heating rate of 1000 ℃ and kept at 600°C for 3 hours to obtain pre-modified graphite felt.

[0041] Step 2: Sputtering the carbon layer using closed-field unbalanced magnetron sputtering ion plating technology:

[0042] 1) The pre-modified graphite felt was fixed on the sample turntable in the vacuum chamber of the closed-field unbalanced magnetron sputtering ion plating device. The turntable speed was set to 3 rpm, and then the vacuum operation was performed until the background vacuum was <4×10 -3 Argon gas was introduced into the vacuum chamber at a flow rate of 25 sccm, and the internal pressure of the vacuum chamber was controlled at 0.1 Pa. A pulse bias of -400 V was applied to the pre-modified graphite felt, and the pre-modified graphite felt was treated with argon plasma for 30 minutes to achieve glow discharge cleaning of the pre-modified graphite felt.

[0043] 2) Maintaining the internal pressure of the vacuum chamber at 0.1 Pa, adjusting the bias voltage to -70 V, controlling the average power to 3 kW, and the deposition time to 1 h, the graphite target was sputtered using a HiPIMS power supply, and a functional nanocarbon layer was deposited on the surface of the pre-modified graphite felt after glow discharge cleaning to obtain a nanocarbon layer-modified graphite felt electrode for all-vanadium liquid flow batteries.

[0044] Example 2

[0045] This embodiment provides a nano-carbon layer modified graphite felt electrode for an all-vanadium redox flow battery, which is prepared by the following steps:

[0046] Step 1: Pre-modification of graphite felt:

[0047] 1) Cut the graphite felt into 3 cm × 3 cm squares and ultrasonically clean them twice with deionized water and anhydrous ethanol, respectively, with each cleaning lasting more than 5 minutes.

[0048] 2) The cleaned graphite felt was placed in a vacuum oven at a preset temperature of 80° C. and dried for 6 h to obtain clean and dry graphite felt.

[0049] 3) Place the clean and dry graphite felt in a muffle furnace and heat it at 5℃·min -1 The temperature was raised to 600°C at a heating rate of 1000 ℃ and kept at 600°C for 3 hours to obtain pre-modified graphite felt.

[0050] Step 2: Sputtering the carbon layer using closed-field unbalanced magnetron sputtering ion plating technology:

[0051] 1) The pre-modified graphite felt was fixed on the sample turntable in the vacuum chamber of the closed-field unbalanced magnetron sputtering ion plating device. The turntable speed was set to 3 rpm, and then the vacuum operation was performed until the background vacuum was <4×10 -3Argon gas was introduced into the vacuum chamber at a flow rate of 25 sccm, and the internal pressure of the vacuum chamber was controlled at 0.1 Pa. A pulse bias of -400 V was applied to the pre-modified graphite felt, and the pre-modified graphite felt was treated with argon plasma for 30 minutes to achieve glow discharge cleaning of the pre-modified graphite felt.

[0052] 2) Maintaining the internal pressure of the vacuum chamber at 0.1 Pa, adjusting the bias voltage to -70 V, controlling the average power to 3 kW, and the deposition time to 3 h, the graphite target was sputtered using a HiPIMS power supply, and a functional nanocarbon layer was deposited on the surface of the pre-modified graphite felt after glow discharge cleaning to obtain a nanocarbon layer-modified graphite felt electrode for all-vanadium liquid flow batteries.

[0053] Comparative Example 1

[0054] This comparative example provides a modified graphite felt, which is prepared by the following steps:

[0055] 1) Cut the graphite felt into 3 cm × 3 cm squares and ultrasonically clean them twice with deionized water and anhydrous ethanol, respectively, with each cleaning lasting more than 5 minutes.

[0056] 2) The cleaned graphite felt was placed in a vacuum oven at a preset temperature of 80° C. and dried for 6 h to obtain clean and dry graphite felt.

[0057] 3) Place the clean and dry graphite felt in a muffle furnace and heat it at 5℃·min -1 The temperature was raised to 600°C at a heating rate of 1000 ℃ and kept at 600°C for 3 hours to obtain a modified graphite felt with a parallel flow channel structure on the fiber surface.

[0058] That is, the difference between this comparative example and Example 1 is only that:

[0059] In this comparative example, no functional nanocarbon layer was deposited.

[0060] Comparative Example 2

[0061] In this comparative example, the original graphite felt that was only cleaned was used as the electrode.

[0062] Experimental part

[0063] (1) Morphology test

[0064] The present invention takes the nano-carbon layer modified graphite felt electrode prepared in Example 1 as an example, and performs a scanning electron microscope test on it, and the test results are as follows: Figure 1 shown.

[0065] Figure 1These are scanning electron microscope images of the nano-carbon layer-modified graphite felt electrode prepared in Example 1. Figure a is a scanning electron microscope image of the nano-carbon layer-modified graphite felt electrode prepared in Example 1 at a 20 μm scale, Figure b is a scanning electron microscope image of the nano-carbon layer-modified graphite felt electrode prepared in Example 1 at a 5 μm scale, and Figure c is a scanning electron microscope image of the nano-carbon layer-modified graphite felt electrode prepared in Example 1 at a 500 nm scale.

[0066] Depend on Figure 1 It can be seen from the test results that the nano-carbon layer modified graphite felt electrode prepared in Example 1 retains the integrity of the multi-channel structure on the surface of the pre-modified carbon felt, but constructs a nano-scale granular carbon layer on the fiber surface. The surface active sites of this nano-carbon layer modified graphite felt with a multi-level active structure are significantly increased.

[0067] (2) Electrochemical performance test

[0068] 1) Cyclic voltammetry test

[0069] The present invention uses the nano-carbon layer modified graphite felt electrode of Example 1, the nano-carbon layer modified graphite felt electrode of Example 2, the modified graphite felt of Comparative Example 1, and the original graphite felt of Comparative Example 2 as the positive electrode and negative electrode of the all-vanadium redox flow battery, respectively, and places them in a three-electrode system for cyclic voltammetry testing, and the testing method is as follows:

[0070] The three-electrode system uses an effective area of ​​1 cm 2 Graphite felt sample with an effective area of ​​1cm 2 Platinum sheet and saturated calomel electrode (SCE) were used as working electrode, counter electrode and reference electrode.

[0071] When used as a positive electrode, the electrolyte is 0.1M V 4+ A mixed solution of 3.0 M H2SO4 was used, with a voltage scan range of 0.3 to 1.4 V and a scan rate of 3 mV·s -1 .

[0072] When used as a negative electrode, the electrolyte is 0.1M V 3+ A mixed solution of 3.0 M H2SO4 was used, with a voltage scan range of -0.8 to -0.1 V and a scan rate of 3 mV·s -1 .

[0073] And the test results are as follows Figure 2 and Figure 3 As shown. Among them, Figure 2 This is a comparison chart of cyclic voltammetry curves of the nano-carbon layer modified graphite felt electrode of Example 1, the nano-carbon layer modified graphite felt electrode of Example 2, the modified graphite felt of Comparative Example 1, and the original graphite felt of Comparative Example 2 when used as positive electrodes. Figure 3This is a comparison chart of cyclic voltammetry curves of the nano-carbon layer modified graphite felt electrode of Example 1, the nano-carbon layer modified graphite felt electrode of Example 2, the modified graphite felt of Comparative Example 1, and the original graphite felt of Comparative Example 2 when used as negative electrodes.

[0074] Figure 2 and Figure 3 In the cyclic voltammetry test, compared with the original graphite felt electrode of Comparative Example 2, the current density of the modified graphite felt electrode of Comparative Example 1 is improved, and the ratio of the peak current density is closer to 1. It can be seen that after heat treatment, the electrochemical reaction activity and reaction reversibility of the electrode are improved.

[0075] Compared with the modified graphite felt electrode of Comparative Example 1, the current density of the nanocarbon layer modified graphite felt electrode of Example 1 is improved, the potential separation of the redox peak is significantly reduced to 378 mV, and the ratio of the peak current density is closer to 1. It can be seen that after the functional nanocarbon layer is constructed, the electrochemical reaction activity and reaction reversibility of the electrode are improved.

[0076] Compared with the nano-carbon layer modified graphite felt electrode of Example 1, the nano-carbon layer modified graphite felt electrode of Example 2 has a lower current density and a larger potential separation of the redox peaks. It can be seen that functional nano-carbon particles of relatively small size are formed on the surface of the graphite felt fibers, which is more conducive to improving the electrochemical reaction activity and reaction reversibility of the electrode.

[0077] 2) Energy efficiency test

[0078] The present invention uses the nano-carbon layer modified graphite felt electrode of Example 1, the nano-carbon layer modified graphite felt electrode of Example 2, the modified graphite felt of Comparative Example 1, and the original graphite felt of Comparative Example 2 as the electrode materials to be tested, and assembles an all-vanadium liquid flow battery according to the following method. The obtained all-vanadium liquid flow battery model is subjected to charge and discharge tests to evaluate the electrochemical performance of the electrode in the liquid flow battery.

[0079] Assembly of all-vanadium redox flow battery:

[0080] Two 3cm x 3cm sections of the electrode material to be tested were used as the positive and negative electrodes, respectively. Both electrodes were surrounded by a polyvinyl chloride frame and connected to a graphite bipolar plate with a serpentine flow channel. Copper plates served as current collectors at each end, and a Nafion 212 separator was used in the middle to separate the positive and negative electrolytes. The entire module was secured with end plates and bolts, and fluororubber gaskets were used for sealing at key connection locations. All-vanadium redox flow batteries corresponding to Example 1, Example 2, Comparative Example 1, and Comparative Example 2 were obtained, respectively.

[0081] Test conditions:

[0082] The all-vanadium redox flow batteries corresponding to the above-mentioned Examples 1, 2, Comparative Examples 1 and 2 were subjected to constant current charge and discharge processes on a NEWARE CT-4008 battery testing system. The charge and discharge cutoff voltages were set to 0.8V and 1.65V, respectively. The operating current density was 50mA·cm -2 ~250mA·cm -2 The initial electrolyte of the positive electrode is 1.7M V 3+ and 3M H2SO4 mixed solution, the initial electrolyte of the positive and negative electrodes is 1.7M VO 2+ The initial electrolyte volume of the positive and negative electrodes was 50 mL, and the electrolyte was driven by a peristaltic pump at a rate of 50 mL min -1 The test cycle number is 20 times. And the test results are as follows Figure 4 shown.

[0083] Figure 4 The vanadium redox flow batteries corresponding to Example 1, Example 2, Comparative Example 1 and Comparative Example 2 are at 50 mA·cm -2 ~250mA·cm -2 Energy efficiency test results at current density of .

[0084] Depend on Figure 4 The test results show that at 100mA·cm -2 At a current density of , the energy efficiency of the all-vanadium liquid flow battery corresponding to Comparative Example 1 is 77.5%, while the energy efficiency of the all-vanadium liquid flow battery corresponding to Comparative Example 2 is 75.9%. That is, compared with Comparative Example 2, the active area of ​​the electrode surface and the electrochemical reaction active sites of Comparative Example 1 are increased, indicating that heat treatment can improve the electrochemical reaction activity of the electrode material, which is beneficial to the improvement of the battery energy efficiency.

[0085] At 100 mA cm -2 At a current density of 250 mA·cm, the energy efficiency of the all-vanadium redox flow battery corresponding to Example 1 is 82.4%, while the energy efficiency of the all-vanadium redox flow battery corresponding to Comparative Example 1 is 77.5%; and at a current density of 250 mA·cm -2 At a high current density, the energy efficiency of the all-vanadium redox flow battery in Example 1 was 71.8%, while the energy efficiency of the all-vanadium redox flow battery in Comparative Example 1 was 61.2%. This indicates that the modification of the pre-modified graphite felt electrode with the surface nanocarbon layer further increases the surface active area of ​​the electrode, thereby increasing the electrode's electrocatalytic activity and improving the battery's cycling performance.

[0086] At 100 mA cm -2At a current density of 250 mA·cm, the energy efficiency of the all-vanadium redox flow battery corresponding to Example 2 is 80.9%, while the energy efficiency of the all-vanadium redox flow battery corresponding to Example 1 is 82.4%; and at a current density of 250 mA·cm -2 At a high current density, the energy efficiency of the all-vanadium redox flow battery in Example 2 was 69.2%, while the energy efficiency of the all-vanadium redox flow battery in Example 1 was 71.8%. This indicates that controlling the size of the functional nanocarbon particles on the graphite felt surface is crucial. Constructing smaller functional nanocarbon particles on the surface is more conducive to improving the electrochemical activity of the graphite felt electrode, thereby achieving better battery efficiency.

[0087] 3) Stability test of coulombic efficiency and energy efficiency

[0088] The present invention takes the all-vanadium redox flow batteries corresponding to the above-assembled embodiment 1 and comparative example 2 as examples, and respectively conducts the experiments at 150 mA·cm -2 The stability of coulombic efficiency and energy efficiency at current density was tested, and the test results are as follows Figure 5 shown.

[0089] Figure 5 The vanadium redox flow battery corresponding to Example 1 and Comparative Example 2 is 150 mA·cm -2 The stability test results of coulombic efficiency and energy efficiency at current density.

[0090] Depend on Figure 5 It can be seen that the all-vanadium redox flow battery corresponding to Example 1 has better electrochemical performance than the all-vanadium redox flow battery corresponding to Comparative Example 2. Although both maintain similar coulombic efficiencies, the energy efficiency of the all-vanadium redox flow battery corresponding to Comparative Example 2 significantly decreases to 59.9% after 200 cycles, while the all-vanadium redox flow battery corresponding to Example 1 still maintains an energy efficiency of 77.2% after 450 cycles. This demonstrates the reliability and stability of the nanocarbon layer-modified graphite felt electrode used in Example 1 during long-term operation.

[0091] Obviously, the above embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

Claims

1. A method for preparing a nano-carbon layer modified graphite felt electrode for an all-vanadium liquid flow battery, characterized in that: The following steps are involved: Using graphite felt as a substrate, cleaning it and then heat treating it to form a parallel flow channel structure on the surface of the graphite felt to obtain a pre-modified graphite felt; Under vacuum conditions, the pre-modified graphite felt is subjected to glow discharge cleaning treatment; Subsequently, under vacuum conditions, a high-power pulsed magnetron sputtering power supply is used as the sputtering power supply, and a graphite target is used as the carbon layer deposition source. A closed-field unbalanced magnetron sputtering ion plating technology is used for sputtering treatment to deposit a layer of functional nanocarbon layer on the surface of the pre-modified graphite felt after glow discharge cleaning treatment, thereby obtaining a nanocarbon layer modified graphite felt electrode with a multi-level active structure on the surface.

2. The preparation method according to claim 1, characterized in that The process parameters during the sputtering process are: The pressure inside the vacuum chamber was maintained at 0.1Pa to 0.2Pa, the bias voltage was adjusted to -100V to -70V, the average power was controlled to 2kW to 4kW, the sample rotation speed was 3rpm to 6rpm, and the deposition time was 0.5h to 5h.

3. The preparation method according to claim 1, characterized in that: The average power delivered by the high-power pulsed magnetron sputtering power supply to a single graphite target is 40 kW to 60 kW.

4. The preparation method according to claim 1, characterized in that: During the sputtering process, the purity of the graphite target material is ≥99.99%.

5. The preparation method according to claim 1, characterized in that: During the sputtering process, the sputtering gas used is argon gas with a purity of ≥99.99%.

6. The preparation method according to claim 1, characterized in that: The sample environment was evacuated to a background vacuum of <4×10 -3 Glow discharge cleaning treatment was performed after Pa; And the process parameters of the glow discharge cleaning treatment are: The argon gas flow rate is 25 sccm to 40 sccm, the pressure inside the vacuum chamber is controlled to be 0.1 Pa to 0.2 Pa, the pulse bias applied to the sample is -400 V to -200 V, the cleaning source of the glow discharge cleaning is argon plasma, and the processing time is 10 min to 30 min.

7. The preparation method according to claim 1, characterized in that: The heat treatment time is 3h to 6h.

8. A nano-carbon layer modified graphite felt electrode prepared by the preparation method according to any one of claims 1 to 7.

9. Use of the nano-carbon layer modified graphite felt electrode according to claim 8 in the preparation of an all-vanadium liquid flow battery.

10. The use according to claim 9, characterized in that The nano-carbon layer modified graphite felt electrode as claimed in claim 8 is used as the electrode.

Citation Information

Cited By

  • Modified graphite felt electrode for all-vanadium redox flow battery and preparation method thereof

    CN120809843B

  • Graphite felt with runner and preparation method thereof

    CN120905936A